The state of cancer care in Russia: cancer of the small intestine (C17). Survival of patients, median survival, survival of patients according to tumor localization, histological pattern and stage of the disease (Population study at the federal district level). Part II - V. M. Merabishvili (Сибирский онкологический журнал)
Background. Small intestine cancer is extremely rare cancer worldwide with an incidence of less than 1.0 per 100,000 population. In 2020, 1,711 cases of small intestine cancer were recorded in Russia, including 781 cases among the male population, and 930 among the female population. It should be noted that in Russia, despite the decrease in the total number of new cancer cases associated with the coronavirus epidemic, the number of patients with small intestine cancer increased by 4.14 % from 2019 to 2020. In the Northwestern Federal district of the Russian Federation, 216 patients with newly diagnosed small intestine cancer were registered in 2020, (29 more patients than in the previous year). The purpose of the study was to analyze the efficiency of small intestine cancer care provision based on of the database of the population cancer Registry (db pcr) of the Northwestern Federal district of the Russian Federation, with an assessment of one- and five-year survival rates. Material and methods. To calculate the survival rates for patients with small intestine cancer, we selected 1922 patients from the database of the pcr of the Northwestern Federal district of the Russian Federation, for the period from 2000 to 2018. Standard methods for calculating survival rates according to the eurocare program were used. Results. The one-year survival rate of small intestine cancer patients increased from 50.0 % to 61.1 % from 2000 to 2018, and the five-year survival rate remained almost unchanged. The relative one-year survival rate of patients was 2.0 % higher. The five-year survival rate for five-year cohorts indicates defects in staging of small intestine cancer rather than an improvement in patient care; although this rate increased from 31.5 to 32.9 %. The histological detail of small intestine cancer according to the icd-10 was investigated. Conclusion. The study confirmed the high mortality rates and modest survival benefits in survival rates in patients with small intestine cancer. Defects in the distribution of patients by disease stages were revealed. The most common histological types of small intestine cancer with calculations of patient survival were identified.